2012
DOI: 10.1016/j.jpedsurg.2012.03.089
|View full text |Cite
|
Sign up to set email alerts
|

Enterocyte expression of epidermal growth factor receptor is not required for intestinal adaptation in response to massive small bowel resection

Abstract: Purpose Intestinal adaptation following massive small bowel resection (SBR) permits improved absorption of enteral nutrition despite significant loss of bowel length. Epidermal growth factor (EGF) and its receptor (EGFR) have previously been established to play major roles in the pathogenesis of adaptation. This study tested the hypothesis that EGFR signaling within the epithelial cell compartment (enterocytes) is required for intestinal adaptation. Methods We developed a tamoxifen-inducible Villin-Cre/LoxP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
3
18
0
1
Order By: Relevance
“…Under normal physiological conditions, adult IEC-Adam17 KO mice are overtly normal and show no significant changes in crypt-villus architecture, crypt proliferation and EBF. This finding is consistent with the lack of intestinal phenotype observed in different IEC-specific EGFR/ErbB-deficient mice (44,45). Moreover, the normal secretory differentiation and viability of IEC-Adam17 KO mice suggests that ADAM17 is not essential for Notch signaling in IECs (37).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Under normal physiological conditions, adult IEC-Adam17 KO mice are overtly normal and show no significant changes in crypt-villus architecture, crypt proliferation and EBF. This finding is consistent with the lack of intestinal phenotype observed in different IEC-specific EGFR/ErbB-deficient mice (44,45). Moreover, the normal secretory differentiation and viability of IEC-Adam17 KO mice suggests that ADAM17 is not essential for Notch signaling in IECs (37).…”
Section: Discussionsupporting
confidence: 87%
“…Taken together, these results indicate that IEC-Adam17 KO mouse model is a suitable model to investigate the contribution of ADAM17 signaling from IECs under different experimental conditions. IEC proliferation is critical for adaptive growth after intestinal injury/inflammation (47,48), and EGFR/ErbB is a major mediator of these IEC responses (44,48,49). In the DSS colitis model, hypomorphic Egfr mice and ErbB ligand-deficient mice display exacerbated intestinal inflammation (50,51), whereas more recent studies using different IEC-ErbB KO mice have shown that all four ErbB receptors contribute, in various degrees, to protection against DSS-induced colitis (19,24,26,45).…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is possible that intestinal mucosal growth is driven by IGF1R stimulation of subepithelial mesenchymal or immune cells. This paradigm is similar to our findings of impaired resection-induced adaptation responses under multiple conditions of global inhibition of epidermal growth factor receptor (EGFR) signaling [28] but preserved responses in mice with genetically disrupted expression of intestinal epithelial EGFR [29]. …”
Section: Discussionsupporting
confidence: 87%
“…The adaptive response is completely blocked in these mice [52]. However, the mechanism by which EGF results in an increased adaptive response remains unclear, as subsequent analyses have shown that the gut-epithelial specific knockout of the EGF receptor does not block the adaptive response [53]. …”
Section: Introductionmentioning
confidence: 99%